Uso dos recursos hídricos para lazer e recreação: diagnóstico e gestão ambiental do balneário do Miriti em Manacapuru - Amazonas - Silva, Claudenei Sampaio da (2018)
The use of water resources for recreation, although it is well known, in the scientific field is still little explored. In this case, the discussion focuses in the Miriti water recreation area located in Manacapuru-AM city. This municipality has several water recreation areas, especially in the rural area and the practice of this kind of leisure has become commom among the residents. The Miriti water recreation area is the most relevant of Manacapuru city and an important tourist destination. Situated on the edge of the Manoel Urbano Highway (AM-070), built in the 1970s, the river area has been experiencing constant environmental damage since then, mostly because of the proximity to the city that collaborates for the water degradation of the Miriti river. Aiming at this, the objective was to propose management guidelines for the sustainable use of the Miriti water recreation area, considering strategies to conserve it in time and space, based on environmental diagnosis. In order to do the study, a bibliographic survey was made about the subject and field work, in order to know the current conditions and to identify the profile of the users. Because it is a public space, the management of the area is in charge of the Municipal Government, which in recent years has not provided management services in Miriti river, which is why it allows damage to the bathing area, including not to discipline the occupation at its banks. The study understands that a public space of leisure, mainly related to water, is of great importance for the Manacapuru citizens and its visitors, who lack appropriate leisure. However, for the improvement and conservation of the area, guidelines are pointed out to be applied in the water recreation area and the river, in order to contribute for managing this important public leisure space.